An investigation of the relationship between Behçet’s disease and tenascin-C - Haydar Kaplan,; Demet Yalcin Kehribar,; Muhammed Okuyucu,; Metin Ozgen, (Archives of Rheumatology, 2024)
Objectives: The study aimed to investigate serum tenascin-C levels and its relationship with pathogenesis of Behçet’s disease (BD) with inflammatory processes. Patients and methods: This prospective and analytical study included 34 BD patients (19 males, 15 females; mean age: 31.5±8.2 years; range, 18 to 48 years) who met the 2014 International Criteria for Behçet's Disease and had no comorbidities and 37 healthy volunteers (21 females, 16 males; mean age: 29.6±5.3 years; range, 21 to 45 years). Sex, age, age at diagnosis, clinical and laboratory data, medication use, and smoking history of the participants were recorded. Serum tenascin-C levels were measured using a commercially available tenascin-C enzyme-linked immunosorbent assay kit. Results: There was no significant difference between the groups in terms of age (p=0.262) and sex (p=0.287). Serum tenascin-C levels were significantly lower in the BD group (10,824±7,612 pg/mL) compared to the control group (27,574±14,533 pg/mL, p<0.001). In the receiver operating characteristic analysis performed for the diagnostic value of tenascin-C level in BD, the sensitivity was determined as 79.4% and the specificity as 82.5% (p<0.001). No statistically significant difference was observed in tenascin-C levels in correlation with clinical characteristics, laboratory values, medication use, and smoking in the BD group. Conclusion: In contrast to other chronic inflammatory diseases, lower levels of tenascin-C were observed in patients with BD than in the healthy individuals, which can be attributed to the absence of prolonged chronic inflammatory course in BD. The fact that tenascin-C levels are high in other rheumatic inflammatory diseases but low in BD may be useful in the differential diagnosis of BD.